The Influence Of Instagram Ads And Celebrity Endorsement On Purchase Decisions In Florist Businesses In Bandar Lampung - Yuspita, Jea; Anggarini, Defia Riski (Jurnal Ekonomi, 2024)
The rise of digital social media technology has significantly impacted business practices in Indonesia, particularly in the florist industry. Businesses are shifting their strategies by leveraging endorsements from viral creators on platforms like Instagram. This shift, while providing new opportunities, also introduces challenges for traditional flower shops that must adapt to social media marketing. The use of social media for flower bouquet marketing through various online exhibitions. This approach aims to boost sales but comes with its own set of obstacles, including competition and content creation difficulties. The florist business in Indonesia, encompassing flower care, design, marketing, merchandising, and delivery, benefits from the cultural significance of flowers, which are used to express emotions and are integrated into various forms of art. In Bandar Lampung, the growth of florist businesses, with 25 shops observed, reflects the promising nature of this industry, driven by its necessity for events such as seminars, weddings, and birthdays. The rapid growth of the flower industry and the emergence of new designs impact consumer purchasing decisions. Effective marketing strategies are crucial for maintaining competitive advantage. With the prevalence of social media in Indonesia, where 167 million users are active, platforms like Instagram play a key role in business promotion. Instagram Ads and endorsements are particularly effective tools, as they reach targeted audiences and enhance brand visibility. This study explores the influence of Instagram Ads and celebrity endorsements on purchase decisions for florist businesses in Bandar Lampung, aiming to provide insights into effective digital marketing strategies in the floral industry.